The Kantian subject new interpretative essays - Silva, Fernando M. F.; Caranti, Luigi 1969- (Routledge, 2024)
"This book presents a critical reconsideration of the Kantian cognitive and practical subject. Special attention is devoted to highlight the complex relation between subjectivity as it is presented in the three critiques and the way in which it is construed in other writings, in particular the Anthropology. While for Kant our cognitive apparatus and the structure of our will are common to all humans, the anthropological subject reveals degrees of variation, depending on a myriad of external circumstances that pose a challenge to the unity of Kant's account and await theoretical solutions. The essays collected in the volume delve into how the different shapes of human nature are not unrelated. They explore how and why different "Kantian subjects" are closely connected and at their core, if not entirely unified. The notions of personality, humanity, and citizenship will serve as leading threads for the reconstruction of this possible underlying unity. An engaging read that promises to deepen our understanding of human nature, the volume will be of great interest to scholars and researchers of philosophy, politics, psychology, social anthropology, ethics, and epistemology"--
2310
Keywords: Kant, Immanuel -- 1724-1804; Subjektivität; Person; Kant, Immanuel / 1724-1804; Subjectivity; Philosophy, German / 18th century; Philosophie allemande / 18e siècle; Aufsatzsammlung